Դիտարկումներ Սևերեկի, Տիգրանակերտի և Եդեսիայի հնչյունական առնչությունների շուրջ - Գևորգյան, Գայանե (ՀՀ ԳԱԱ ԼԻ հրատ.)
The phonetic relations of Severek, Tigranakert and Edesia are considered in the article. The selection of the above-mentioned dialect units is due to the fact that all three dialect units are located in northern Mesopotamia in the neighborhood. By phonetic features, the speech of Severek is similar to the dialects of Edesia and Tigranakert, sometimes within the boundaries of one or another sign, a combination of various dialectal features is manifested. for example, before the diphthong ai there is a phonetic change ай>а (Edesiya) and ай>е (Tigranakert). В статье рассматриваются фонетических соотношених Северека, Тигранакерта и Эдесии. Выбор вышеупомянутых диалектных единиц обусловлен тем, что все три диалектные единицы расположены в северной Месопотамии по соседству. По фонетическим особенностям говор Северека сходна с диалектами Эдесии и Тигранакерта, иногда в границах того или иного признака проявляется сочетание различных диалектных особенностей. например, перед дифтонгом ai есть фонетическое изменение ай>а (Эдесия) и ай>е (Тигранакерт).
Keywords: Բարբառագիտություն; Հնչյունաբանություն